Molecular conservation of marsupial and eutherian placentation and lactation - Guernsey, Michael W (eLife, 2017)
Eutherians are often mistakenly termed ‘placental mammals’, but marsupials also have a placenta to mediate early embryonic development. Lactation is necessary for both infant and fetal development in eutherians and marsupials, although marsupials have a far more complex milk repertoire that facilitates morphogenesis of developmentally immature young. In this study, we demonstrate that the anatomically simple tammar placenta expresses a dynamic molecular program that is reminiscent of eutherian placentation, including both fetal and maternal signals. Further, we provide evidence that genes facilitating fetal development and nutrient transport display convergent co-option by placental and mammary gland cell types to optimize offspring success. DOI: http://dx.doi.org/10.7554/eLife.27450.001